Structural Optimization of (Aum‐Agn‐Pdo‐Ptp) (m=10 and n+o+p=10) Tetrametallic Clusters Using a Combined Empirical Potential‐Density Functional (EP‐DF) Approach. Issue 26 (19th September 2017) - Srivastava, Ruby
Abstract: The putative global minimum structures of (Aum ‐Agn ‐Pdo ‐Ptp ) (m=10 and n+o+p=10) tetrametallic clusters with 20 atoms are obtained by basin hopping algorithm using Gupta potential parameters. A system‐comparison approach through combined empirical potential (EP)‐density functional (DF) method is adopted to investigate the energy competition and segregation effect for thirty six structural motifs. Vibrational analysis has been carried out to check the stability of these doped metal clusters. The thermal and chemical stability are measured by binding energy and HOMO‐LUMO gap. We have calculated the excess mixing energy, mixing energy and mixing coefficient, order parameter, average nearest neighbor distance (ANND) and shape deformation parameter for these doped metal clusters. Mixing/segregation effect is also discussed. Overall the calculated energy by EP parameters is lower for moderate number of (Pt, Pd) or higher number of Pt atoms and reasonably accurate for the other doped clusters. Results show that Au and Ag atoms occupy the surface sites while Pt and Pd atoms prefer mostly to the inner and middle shell. Abstract : The putative global minimum structures of (Aum ‐Agn ‐Pdo ‐Ptp ) (m=10 and n+o+p=10) tetrametallic clusters with twenty atoms are obtained by basin hopping algorithm using Gupta potential parameters. A system‐comparison approach through combined empirical potential (EP)‐density functional (DF) method is adopted to investigate various parameters and segregation effect for thirty six structural motifs using various parameters. The thermal and chemical stability of these doped metal are measured by binding energy and HOMO‐LUMO gap.